Preservation of the cystic artery during laparoscopic cholecystectomy: Current state of the problem - Khalikov S.P; Jumanazarov A.U; Uktamov M.X (Zien Journals, 2026)
Laparoscopic cholecystectomy remains the standard surgical treatment for gallstone disease; however, injuries to the extrahepatic bile ducts and combined vasculobiliary complications continue to represent a serious clinical problem. In most cases, these complications are associated with erroneous identification of anatomical structures within the hepatocystic triangle. In this context, increasing attention is being paid to the concept of safe cholecystectomy and to organ-preserving elements of surgical technique, including preservation of the cystic artery.
Keywords: laparoscopic cholecystectomy; cystic artery